The Influence of Product Innovation and Organizational Innovation On Culinary Business Performance Of Small And Medium Enterprises - Salma, Ashfia Syahidatu; Hamdani, Nizar Alam; Nugraha, Sukma (Entrepreneurship Faculty, Universitas Garut, 2023)
This research discusses how product and organizational innovation influence business performance. The population of this research is West Java culinary MSMEs, one of which is Garut Regency. This type of research is quantitative research with a descriptive approach. The sample used in this research was 100 Culinary MSME entrepreneurs in Garut Regency, using a purposive sampling technique and the Smart PLS version 4.0 supporting tool by distributing questionnaires via Google Forms. This research examines the influence of product and organizational innovation on business performance. This research aims to determine the influence of independent variables that can influence business performance apart from research that has been conducted previously. The analysis used in this research is the outer model test, inner model test, and hypothesis test, which was carried out using the total effect. The results of this research state that product innovation influences 48.6%. The organizational innovation variable has an influence of 27.8% on business performance. This third variable shows that variables can control each other with sufficient or moderate value. The aim is to test the influence of product and organizational innovation on business performance.